A sludge ash modified tin oxide composite electrocatalyst and its preparation method and application

By modifying the tin oxide composite electrocatalyst by sludge ash, the alkalinity and acidity of the electrocatalyst are enhanced by using the metal elements rich in sludge ash, the problems of insufficient CO2 adsorption capacity of the tin oxide electrocatalyst and insufficient improvement of the H2O oxidation semi-reaction are solved, and efficient CO2 reduction and formic acid preparation are achieved.

CN115679369BActive Publication Date: 2025-04-29HEFEI CEMENT RESEARCH AND DESIGN INSTITUTE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211434102.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-16
Publication Date
2025-04-29
Estimated Expiration
2042-11-16

AI Technical Summary

Technical Problem

During the electrocatalytic reduction of CO2 to formic acid, the CO2 adsorption capacity is insufficient and the H2O oxidation semi-reaction is insufficient, resulting in low electrical reduction efficiency.

Method used

By mixing the sludge ash with tin oxide, the iron, aluminum, magnesium, calcium and other elements rich in the sludge ash can be used to enhance the overall alkalinity and part of the Lewis acidity of the electrocatalyst, thereby improving the CO2 adsorption performance and H2O oxidation semi-reactive activity.

Benefits of technology

It significantly improves CO2 adsorption efficiency and electrocatalytic reduction of CO2 to make formic acid, reduces production costs, and realizes solid waste resource utilization.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a sludge ash modified tin oxide composite electrocatalyst and a preparation method and application thereof, and relates to the technical field of electrocatalysts. The sludge ash modified tin oxide composite electrocatalyst comprises sludge ash and tin oxide loaded on the sludge ash. The sludge ash modified tin oxide electrocatalyst provided by the invention has main gain components all coming from the incineration ash of sludge, a by-product of a sewage treatment plant, and belongs to the resource utilization of solid waste, thereby effectively reducing the production cost of the composite electrocatalyst. Moreover, the strategy of the sludge ash modified tin oxide electrocatalyst provided by the invention to simultaneously promote reduction and oxidation half-reactions will open up a new way for preparing high-efficiency electrocatalysts for electroreduction of CO2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention relates to the technical field of electrocatalysts, and in particular to a sludge ash modified tin oxide composite electrocatalyst and a preparation method and application thereof. Background technology:

[0002] Under the background of my country's "dual carbon" strategy, with the development and large-scale popularization of green electricity, as well as the unique advantages of electrocatalytic technology such as mild reaction conditions, simple system structure, easy modularization and controllable reaction scale, electrocatalytic reduction of CO2 has broad commercial prospects.

[0003] Among the many electro-reduction products, formic acid is the product with the highest unit economic benefits, so the production of formic acid by electrocatalytic reduction of CO2 has important practical significance. Electrocatalytic materials are the core of electrocatalytic reduction of CO2 to formic acid. Nano-tin oxide electrocatalysts are widely used in electrocatalytic reduction of CO2 to formic acid, and have the advantages of good chemical stability, non-toxicity, recyclability and low cost. However, there are some defects in the electrocatalytic reduction of CO2 to formic acid, such as the insufficient adsorption capacity of tin oxide for CO2 molecules, resulting in low electro-reduction efficiency. Most of the existing tin oxide modification measures are aimed at the CO2 reduction half-reaction, while the improvement measures for the H2O oxidation half-reaction are insufficient. Therefore, how to improve the adsorption capacity of tin oxide for CO2 while strengthening the H2O oxidation half-reaction, thereby improving the overall electro-reduction efficiency, is particularly critical.

[0004] At present, the existing patented technology mainly loads some organic amines, such as polyacrylamide, on the surface of tin oxide to form an aminated film to improve the adsorption of CO2. However, organic amines are expensive and the loading process is complicated, which increases the cost. Summary of the invention:

[0005] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a sludge ash modified tin oxide composite electrocatalyst, which makes full use of elements such as iron, aluminum, magnesium, calcium, etc. in the incineration ash to enhance the overall alkalinity and partial Lewis acidity of the electrocatalyst, has the advantages of low cost, high CO2 adsorption efficiency, and can significantly enhance the H2O oxidation half reaction, thereby improving the efficiency of electrocatalytic CO2 reduction to produce formic acid.

[0006] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0007] The first object of the present invention is to provide a sludge ash modified tin oxide composite electrocatalyst, comprising sludge ash and tin oxide supported on the sludge ash.

[0008] The second object of the present invention is to provide a method for preparing the sludge ash modified tin oxide composite electrocatalyst, comprising the following steps:

[0009] (1) calcining municipal sludge, grinding to obtain sludge ash for later use;

[0010] (2) mixing the sludge ash obtained in step (1) with tin oxide, grinding, adding acid to adjust the pH value to 1-2, stirring, adding alkali to adjust the pH value to 8-9, and filtering to obtain a mixed solid;

[0011] (3) The mixed solid obtained in step (2) is placed in a vacuum furnace and calcined to obtain a sludge ash-modified tin oxide electrocatalyst.

[0012] The third object of the present invention is to provide a sludge ash modified tin oxide composite electrocatalyst obtained according to the above preparation method.

[0013] The fourth object of the present invention is to provide the use of the sludge ash modified tin oxide composite electrocatalyst in the electrocatalytic reduction of CO2 to produce formic acid.

[0014] Compared with the prior art, the present invention has the following technical effects:

[0015] 1. The sludge ash modified tin oxide electrocatalyst provided by the present invention has its main gain components all coming from the incineration ash of the sludge byproduct of the sewage treatment plant, which belongs to the resource utilization of solid waste, effectively reduces the production cost of the composite electrocatalyst, and has broad market application prospects;

[0016] 2. The sludge ash-modified tin oxide electrocatalyst provided by the present invention has strong alkalinity, can greatly improve the CO2 adsorption performance, improve the mass transfer resistance from the water phase to the solid phase during the CO2 electroreduction process, and can promote the CO2 reduction half-reaction;

[0017] 3. The sludge ash-modified tin oxide electrocatalyst provided by the present invention has partial Lewis acidity and can serve as an active site for H2O adsorption and activation, thereby promoting the H2O oxidation half-reaction;

[0018] 4. The strategy of using sludge ash to modify tin oxide electrocatalysts to promote both reduction and oxidation half-reactions provided by the present invention will open up a new approach for preparing efficient electrocatalysts for the electroreduction of CO2.

[0019] 5. The preparation method of the sludge ash modified tin oxide electrocatalyst provided by the present invention has the advantages of simple operation and all raw materials are cheap and easily available. Specific implementation method:

[0020] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.

[0021] The invention provides a sludge ash modified tin oxide composite electrocatalyst, comprising sludge ash and tin oxide loaded on the sludge ash.

[0022] In the present invention, the composite electrocatalyst uses tin oxide and metal oxides contained in sludge ash as active components.

[0023] The sludge ash modified tin oxide composite electrocatalyst comprises 20-40% tin oxide and 60-80% sludge ash, calculated in weight percentage.

[0024] The present invention also provides a method for preparing the sludge ash modified tin oxide composite electrocatalyst, comprising the following steps:

[0025] (1) calcining municipal sludge, grinding to obtain sludge ash for later use;

[0026] (2) mixing the sludge ash obtained in step (1) with tin oxide, grinding, adding acid to adjust the pH value to 1-2, stirring, adding alkali to adjust the pH value to 8-9, and filtering to obtain a mixed solid;

[0027] (3) The mixed solid obtained in step (2) is placed in a vacuum furnace and calcined to obtain a sludge ash-modified tin oxide electrocatalyst.

[0028] In the present invention, the purpose of calcining municipal sludge is to remove organic matter therein to obtain sludge ash, while ensuring that the active components therein are in a relatively stable state when used. The municipal sludge is calcined at 500-700°C in an air atmosphere for 2-6 hours. Preferably, the municipal sludge is calcined at 600°C in an air atmosphere for 4 hours.

[0029] In the present invention, the mass fraction of calcium compounds in the sludge ash is ≥10%, the mass fraction of iron compounds is ≥10%, and the mass fraction of magnesium and aluminum compounds is ≥10%.

[0030] In the present invention, in order to ensure that CO2 of different concentrations can be effectively adsorbed and activated, and to ensure that after the addition of sludge ash and tin oxide from different sources, the main active ingredients and the auxiliary active ingredients in the composite electrocatalyst can exist in a suitable ratio to regulate the catalytic activity, the weight ratio of the sludge ash and tin oxide is 1: (0.25-0.67).

[0031] In the present invention, the acid includes but is not limited to one or more of hydrochloric acid, sulfuric acid, and nitric acid, and the concentration is 0.05-0.2 mol / L. Preferably, the acid is hydrochloric acid.

[0032] In the present invention, the alkali includes but is not limited to one or more of sodium hydroxide, potassium hydroxide, and ammonia water, and the concentration is 0.05-0.2 mol / L. Preferably, the alkali is ammonia water.

[0033] In the present invention, the calcination temperature of the mixed solid is 350-550°C, and the calcination time is 0.5-2h. The purpose of calcining the mixed solid is to allow the active metals in the sludge ash to form oxide components and form chemical bonds with tin oxide to enhance the electronic conductivity. Preferably, the calcination temperature of the mixed solid is 450°C, and the calcination time is 1h.

[0034] The present invention also provides a sludge ash modified tin oxide composite electrocatalyst obtained according to the preparation method.

[0035] The present invention also provides the use of the sludge ash modified tin oxide composite electrocatalyst in the electrocatalytic reduction of CO2 to produce formic acid. Preferably, the amount of the sludge ash modified tin oxide composite electrocatalyst is 1-5 mg / cm 2 , where cm 2 It is measured based on the area of ​​the working electrode.

[0036] The technical concept of the technical solution provided by the present invention is to use sludge ash to modify the tin oxide composite electrocatalyst, make full use of the sludge ash rich in alkaline elements such as magnesium, aluminum, calcium to improve the CO2 adsorption performance, promote the CO2 reduction half reaction and Lewis acidic elements such as iron to strengthen H2O adsorption and activation, H2O oxidation half reaction, and improve the efficiency of tin oxide electrocatalyst electrocatalytic reduction of CO2 to produce formic acid.

[0037] The sludge ash modified tin oxide composite electrocatalyst of the present invention has acid-base amphotericity, excellent CO2 adsorption performance, excellent H2O adsorption and activation performance, high efficiency of electrocatalytic reduction of CO2, simple operation, and can realize resource utilization of solid waste.

[0038] The sludge ash modified tin oxide composite electrocatalyst provided by the present invention is further described below through specific examples.

[0039] Example 1

[0040] (1) The municipal sludge was calcined at 600°C in air for 4 hours, and then taken out and ground to obtain sludge ash after cooling to room temperature. After testing, the composition of sludge ash includes, by mass percentage, 28.6% silicon oxide, 20% iron oxide, 9.7% aluminum oxide, 16.3% calcium oxide, 22.5% phosphorus pentoxide, 3% magnesium oxide, and the rest are trace compounds such as sodium, potassium, and sulfur.

[0041] (2) 7 g of sludge ash and 3 g of tin oxide were mixed evenly, ground, and 100 mL of 0.1 M dilute hydrochloric acid solution was added to adjust the pH value to 2, and the mixture was stirred for 30 min; then 150 mL of 0.1 M ammonia water was added to adjust the pH value to 8, and the mixed solid was obtained by filtration.

[0042] (3) placing the mixed solid obtained in step (2) in a vacuum furnace, calcining at 450° C. for 1 hour, and cooling to room temperature. The obtained solid product is the sludge ash-modified tin oxide composite electrocatalyst.

[0043] Performance Test:

[0044] The test process adopts a standard three-electrode system and is carried out on an electrochemical workstation. The test reactor is a customized H-type electrolytic cell separated by a Nafion117 proton exchange membrane. 10 mg of the composite electrocatalyst prepared in this example is weighed and dispersed in 1 mL of isopropanol solution, and 40 μL of 5 wt% Nafion solution is added. After ultrasonic dispersion for 1 hour, a dispersion containing the composite electrocatalyst is obtained. 100 μL of the dispersion is dropped and applied to a 1×1 cm 2 The carbon paper was used as the working electrode, and the platinum sheet and Ag / AgCl electrode were used as the counter electrode and reference electrode, respectively. The cathode area of ​​the electrolytic cell was a 0.1 mol / L KHCO3 solution. Before the electrochemical test, N2 and CO2 were introduced into the solution for 30 minutes to saturate the solution. The reduction potential range of the constant voltage electrolysis test was -1.6 to -2.4 V vs Ag / AgCl, and the reduction time was 2 hours. The electrolyte in the cathode area of ​​the reactor was detected using an ion chromatograph, and the formic acid Faraday efficiency was calculated. The results showed that under the voltage condition of -2.0 V vsAg / AgCl, the formic acid Faraday efficiency was 80.1% and the hydrogen yield was 10.4%.

[0045] Example 2

[0046] The difference between the preparation method of the composite electrocatalyst in this embodiment and that in embodiment 1 is that the calcination temperature of the sludge ash in step (1) is 500° C. and the calcination time is 2 h; the other conditions remain unchanged to prepare the composite electrocatalyst.

[0047] The performance test was carried out according to the method of Example 1. The results showed that the formic acid Faradaic efficiency was 65.9% and the hydrogen yield was 8.7%.

[0048] Example 3

[0049] The difference between the preparation method of the composite electrocatalyst in this embodiment and that in embodiment 1 is that the calcination temperature of the mixed solid in step (3) is 500° C. and the calcination time is 2 h; the other conditions remain unchanged to prepare the composite electrocatalyst.

[0050] The performance test was carried out according to the method of Example 1. The results showed that the formic acid Faradaic efficiency was 56.8% and the hydrogen yield was 9.0%.

[0051] Comparative Example 1

[0052] The difference between the preparation method of the composite electrocatalyst in this comparative example and that in Example 1 is that in step (2), 5 g of sludge ash and 5 g of tin oxide are uniformly mixed and ground; the other conditions remain unchanged to prepare the composite electrocatalyst.

[0053] The performance test was carried out according to the method of Example 1. The results showed that the formic acid Faradaic efficiency was 60.3% and the hydrogen yield was 6.5%.

[0054] Comparative Example 2

[0055] The difference between the preparation method of the composite electrocatalyst in this comparative example and Example 1 is that the components of the sludge ash used are, by mass percentage, 26% silicon oxide, 3% iron oxide, 6% aluminum oxide, 24% calcium oxide, 17% phosphorus pentoxide, 2% magnesium oxide, and the rest are trace compounds such as sodium, potassium, and sulfur; the other conditions remain unchanged, and the composite electrocatalyst is prepared.

[0056] The performance test was carried out according to the method of Example 1. The results showed that the formic acid Faraday efficiency was 54.1% and the hydrogen yield was 4.5%.

[0057] Comparative Example 3

[0058] In this comparative example, tin oxide is directly used as the electrocatalyst, and the amount of tin oxide used is equal to the amount of tin oxide contained in the composite electrocatalyst prepared in Example 1.

[0059] The performance test was carried out according to the method of Example 1. The results showed that the formic acid Faradaic efficiency was 50.4% and the hydrogen yield was 3.8%.

[0060] It can be seen from the above embodiments and comparative examples that the technical solution provided by the present invention enhances the adsorption capacity of tin oxide for CO2 and promotes the H2O oxidation half-reaction by modifying tin oxide with sludge ash, thereby improving the overall electrocatalytic reduction efficiency of the catalyst for producing formic acid.

[0061] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. Application of a sludge ash modified tin oxide composite electrocatalyst in electrocatalytic reduction of CO2 to produce formic acid, the sludge ash modified tin oxide composite electrocatalyst comprising sludge ash and tin oxide supported on the sludge ash; The preparation method of the sludge ash modified tin oxide composite electrocatalyst comprises the following steps: (1) calcining municipal sludge, grinding and obtaining sludge ash for later use; (2) mixing the sludge ash obtained in step (1) with tin oxide, grinding, adding acid to adjust the pH value to 1-2, stirring, adding alkali to adjust the pH value to 8-9, and filtering to obtain a mixed solid; (3) The mixed solid obtained in step (2) is placed in a vacuum furnace and calcined to obtain a sludge ash-modified tin oxide electrocatalyst.

2. The use according to claim 1, characterized in that: The sludge ash modified tin oxide composite electrocatalyst comprises 20-40% tin oxide and 60-80% sludge ash, calculated in weight percentage.

3. The use according to claim 1, characterized in that: The municipal sludge is calcined at 500-700° C. in an air atmosphere for 2-6 hours.

4. The use according to claim 3, characterized in that: The municipal sludge was calcined at 600°C in air atmosphere for 4 h.

5. The use according to claim 1, characterized in that: The mass fraction of calcium compounds in the sludge ash is ≥10%, the mass fraction of iron compounds is ≥10%, and the mass fraction of magnesium and aluminum compounds is ≥10%.

6. The use according to claim 1, characterized in that: The weight ratio of the sludge ash to tin oxide is 1: (0.25-0.67).

7. The use according to claim 1, characterized in that: The acid is one or more of hydrochloric acid, sulfuric acid, and nitric acid, and the concentration is 0.05-0.2 mol / L; The alkali is one or more of sodium hydroxide, potassium hydroxide and ammonia water, and the concentration is 0.05-0.2 mol / L.

8. The use according to claim 7, characterized in that: The acid is hydrochloric acid; the base is aqueous ammonia.

9. The use according to claim 1, characterized in that: The calcination temperature of the mixed solid is 350-550° C., and the calcination time is 0.5-2 h.

10. The use according to claim 9, characterized in that: The calcination temperature of the mixed solid is 450° C., and the calcination time is 1 hour.

11. The use according to claim 1, characterized in that: The amount of the sludge ash modified tin oxide composite electrocatalyst is 1-5 mg / cm 2 .

Citation Information

Patent Citations

  • Novel efficient resource utilization method of electroplating sludge and carbon dioxide co-processing

    CN105601074A

  • Sludge ash modified titanium oxide-biochar composite photocatalyst as well as preparation method and application thereof

    CN113522264A